Global technology innovation: comparison of new broad-based index of financial development of Europe and Asia - Fakhrullah; Sher Khan; Xiao DingDing; Marian Suplata (Future Business Journal)
Abstract Financial development plays a vital role in fostering economic growth, influencing financial institutions, markets, technological innovation, and gross domestic product (GDP). While prior research has extensively examined this relationship, traditional metrics such as the ratio of private credit to GDP and stock market capitalization to GDP fail to capture the multidimensional nature of financial development. To address this limitation, this study introduces nine comprehensive measures encompassing financial depth, access, and efficiency across financial institutions and markets. Using a dataset spanning 2019–2022, this study evaluates financial development indicators for countries listed from A to L in the International Monetary Fund database. The findings reveal a robust positive correlation between financial development and technological innovation, suggesting that enhanced financial infrastructure facilitates technological advancements. Moreover, the results indicate a significant positive relationship between technological innovation and GDP, reinforcing the argument that innovation serves as a catalyst for economic expansion. These findings underscore the critical role of financial development in not only promoting innovation but also in stimulating economic growth. The study carries important implications for policymakers, emphasizing the necessity of financial sector reforms to enhance financial access, depth, and efficiency. By fostering a more developed financial system, nations can stimulate technological progress and, consequently, economic growth. The inclusion of nine financial development measures provides a more holistic evaluation compared to traditional metrics, offering deeper insights into the dynamics of financial systems. In conclusion, this study contributes to the literature by presenting a more nuanced understanding of financial development’s impact on technological innovation and GDP, highlighting its essential role in shaping sustainable economic growth. Graphical abstract